Huwaran/hulmahan atbp. the film writings of Johven Velasco - Velasco, Johven 1948-2007 (University of the Philippines Press, 2009)
A compilation of film articles by Johven Velasco and his contribution as a film director, educator and writer in the film industry in the Philippines.